Aerodynamic Optimization of the Cessna 172 Propeller via Computational Fluid Dynamics - Temirel, Mikail; Gördebil, Mehmet Ali (My University, 2025)
The term “Light Aircraft” refers to aircraft weighing less than 5.5 tons. The term light aircraft refers to aircraft weighing less than 5.5 tons. These aircraft formed the backbone of air forces during both world wars, primarily powered by propellers, and continue to be widely used today for flight training, travel, recreation, and personal use. Cessna, a leading light aircraft manufacturer, introduced the Cessna 172 in 1956—a model that remains in production. However, its limited speed and altitude performance fall short of modern aviation requirements. To address these limitations, a computational fluid dynamics (CFD) study was conducted using Ansys Fluent and CFX to enhance the aircraft’s aerodynamic efficiency and speed. Design modifications were applied to the propeller, with a focus on improving thrust generation. The modified configuration produced a significant improvement: CFD results indicated an approximately 50% increase in thrust, corresponding to a 21% increase in the maximum velocity of the aircraft. This study highlights the potential of CFD tools to optimize classic aircraft designs such as the Cessna 172, providing practical insights for the modernization of light aircraft in both civilian and military applications.
Keywords: Mühendislik, Hava Ve Uzay